2020
DOI: 10.1017/s0014479720000253
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of technical efficiency of potato farmers and effects of constraints on potato production in Northern Ethiopia

Abstract: To improve the national average yield of potato in Ethiopia, which is very low as compared to its potential, factors that influence technical efficiency of potato production need to be determined. Therefore, the objective of this study was to investigate the determinants of technical efficiency using a cross-sectional data collected from 368 randomly selected potato producers in Northern Ethiopia using a multi-stage sampling technique. The study employed Cobb–Douglas stochastic frontier model to get farm-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
5
8
0
Order By: Relevance
“…Finally, application of agrochemicals also significantly affected tef yield at 1%, and increasing chemical application by 1% increase yield by 0.064%. This result is in line with the results reported by other scholars (Mburu et al, 2014;Okello et al, 2019;Wassihun et al, 2019;Andaregie and Astatkie, 2020;Belete, 2020).…”
Section: Estimation Of Maximum Likelihoodsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, application of agrochemicals also significantly affected tef yield at 1%, and increasing chemical application by 1% increase yield by 0.064%. This result is in line with the results reported by other scholars (Mburu et al, 2014;Okello et al, 2019;Wassihun et al, 2019;Andaregie and Astatkie, 2020;Belete, 2020).…”
Section: Estimation Of Maximum Likelihoodsupporting
confidence: 93%
“…Moreover, household heads having more experience in tef production were more efficient compared to less experienced farm households. This result is in line with the findings reported by (Wassihun et al, 2019;Andaregie and Astatkie, 2020;Belete, 2020;Khan et al, 2022).…”
Section: Estimation Of Maximum Likelihoodsupporting
confidence: 93%
“…This could be because experience in producing haricot bean gives farmers a chance to identify production and marketing challenges and identify who needs and when they need haricot bean output. This is in line with what was reported on a different crop where the experience of smallholder potato producers positively and significantly influences technical efficiency in Northern Ethiopia (Andaregie & Astatkie, 2020).…”
Section: Second Step Ols Estimation Of the Regression Modelsupporting
confidence: 91%
“…In Ethiopia, the productivity and production of grain legumes are below its potential, primarily due to low input usage, limited availability of seed, lack of extension services, and market problems (Kebede, 2020). However, Andaregie and Astatkie (2020) reported that access to the product market and the experience of smallholder potato producers significantly influence the efficiency and marketing of potato output in Northern Ethiopia. These factors may also influence the efficiency and marketing of the haricot bean.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation